Working Group on Issues Relating to Growth and Development at Sub-National Level (2012-17) - Planning Commission (Planning Commission, 2012)
Planning Commission is in the process of formulating the Twelfth Five Year Plan. Basic objective of the Twelfth Five Year Plan is: Faster, More Inclusive, and Sustainable Growth. For growth to be more inclusive we need better performance in agriculture, faster creation of jobs, especially in manufacturing, stronger efforts at health, education and skill development, improve effectiveness of programmes directly aimed at the poor, special programmes for socially vulnerable groups, and special plans for disadvantaged/ backward regions. To have balanced regional development, it is very important to look into the growth and development issues concerning the underperforming regions. In this context, the indicators which are important from the point of view of policy interventions to achieve the objective of broad, faster and inclusive growth needs to be identified. Analysis of contribution of sectoral GSDP to total GSDP, income and consumption data and infrastructure development at sub-national level may help in policy formulation.
Planning Commission Yojana Bhavan, Sansad Marg New Delhi